The influence of emotional intelligence and self-esteem among employee towards organizational commitment in public sector - Johar, Siti Sarawati (Global Journals Inc. (USA), 2012)
Emotional intelligence currently growing attention and earn a spot in the form of psychological studies. Emotional intelligence detected can influence employee commitment in an organization. The theoretical solutions are simply not able to unlock the psychological issues in organizations because it is closely linked to affective, cognitive and human behavior in public sector. In this study, the issues in the workplace are referring to emotional intelligence, selfesteem and commitment of employees..